2013
DOI: 10.1530/eje-12-0288
|View full text |Cite
|
Sign up to set email alerts
|

A cohort effect on serum testosterone levels in Finnish men

Abstract: Objective: To investigate whether a population-level decline in serum testosterone exists in Finnish men. In comparison with other European populations, Finnish men have compared well in the studies of reproductive health (i.e. semen quality, incidence of cryptorchidism and testicular cancer); thus, we expected no significant cohort-dependent decrease in serum testosterone. Methods: We analysed serum levels of testosterone, gonadotrophin and sex hormone binding globulin (SHBG) in 3271 men representing differen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
27
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 52 publications
(32 citation statements)
references
References 22 publications
1
27
0
Order By: Relevance
“…There is also evidence of an increase in the number of boys with congenital abnormalities of the genitalia [59,60,61,62]. Finally, investigators from the USA and Europe have reported lower serum testosterone levels among normal men [63,64,65]. …”
Section: Perspectives and Conclusionmentioning
confidence: 99%
“…There is also evidence of an increase in the number of boys with congenital abnormalities of the genitalia [59,60,61,62]. Finally, investigators from the USA and Europe have reported lower serum testosterone levels among normal men [63,64,65]. …”
Section: Perspectives and Conclusionmentioning
confidence: 99%
“…Cross-sectional studies have associated low testosterone levels with increased cardiovascular risk factors (diabetes mellitus, the metabolic syndrome, abnormal lipid profile) and increased cardiovascular risk in men. 25 This is particularly important given the progressive population-level decline in serum testosterone concentrations in men from developed countries 68 which has resulted in a dramatic increase in the use of androgen replacement therapy (ART). Indeed, there has been a 10-fold increase in prescribed ART in the USA 9 and nearly a 3-fold increase in the UK 10 in the past decade.…”
Section: Introductionmentioning
confidence: 99%
“…Such fetal programming applies to common disorders encapsulated in the metabolic syndrome (2), which are interlinked in adult men with low testosterone levels (3). Large studies from the United States (4) and Europe (5,6) also show that testosterone levels in men of all ages are declining with later year of birth. Aging is itself associated with declining testosterone levels and a high incidence of primary/compensated hypogonadism (7)(8)(9).…”
mentioning
confidence: 99%